Situation Report: Hungary, 29 July 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Suggestions for the Handling of Collective Farm Labor Disputes A New Proposal for Private Plot Farming Agricultural Co-operation between Hungary and France Restrictions on Foreign Currency Accounts Eased for Hungarians The Tourist Industry: A Mid-year Report Biro Praises Foreign Trade Development for 1969 Latest Developments on Hungary's GATT Application Hungarian-Canadian Potash Deal in Difficulty Are the Communist Faithful Dwindling? (II) Coverage of Moon Landing